Nasal Septal Perforation Reconstruction with Polydioxanone Plate: A Systematic Review - Levin, Marc; Ziai, Hedyeh; Shapiro, Justin; Roskies, Michael G. (Facial Plastic Surgery, 2022)
Nasal septal perforation is an uncommon pathology that is difficult to surgically repair and may significantly impact patients' quality of life. Existing treatments have high complication and failure rates. The use of polydioxanone (PDS) plates to repair septal perforations is an innovative approach that has demonstrated superior outcomes to the conventional techniques. This study aimed to review the literature on PDS plates for nasal septal perforation reconstruction. PubMed, OVID Medline, and OVID Embase databases were searched for relevant articles in June 2021. Search terms included nasal septal perforation, polydioxanone, septal perforation, septal repair, nasal septum, and PDS plate. The Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) guidelines were adhered to for this systematic review. Database searches yielded 80 articles. Seven articles were included representing 74 patients. All studies reported the use of PDS plates in addition to other materials. They all reported closure rates of at least 80%. The majority of studies reported no postoperative complications. Nasal septal perforation reconstruction with PDS plates is a promising approach that has demonstrated positive outcomes. Further larger studies are required to evaluate the long-term efficacy of using PDS plates on patients with septal perforations.
Keywords: nasal septal perforation; septal reconstruction; PDS plate; polydioxanone plate